2012
DOI: 10.1002/jbmr.1716
|View full text |Cite
|
Sign up to set email alerts
|

Antiresorptives overlapping ongoing teriparatide treatment result in additional increases in bone mineral density

Abstract: During teriparatide (TPTD) treatment, high levels of bone formation are accompanied by an increase in bone resorption. The aim of this work was to test if coadministration of raloxifene (RAL) or alendronate (ALN) following 9 months of ongoing TPTD therapy would reopen the anabolic window, thereby exerting additional benefit on bone mineral density (BMD). Postmenopausal women (n ¼ 125) with severe osteoporosis on TPTD treatment for 9 months were randomized into three open-label groups for a further 9 months: AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 42 publications
2
58
0
1
Order By: Relevance
“…6,8,31,32 Treatment using teriparatide is associated with a significant increase of bone mass in the lumbar spine. 14,26,28,44 We previously reported that teriparatide administered daily for 2 months before surgery reduced the incidence of pedicle screw loosening after instrumented lumbar fusion in postmenopausal women with osteoporosis, suggesting that teriparatide increased not only bone mass, but also the quality of the pedicle cortex. 34 However, a clinical study of the effect of teriparatide on pedicle screw insertional torque in postmenopausal women with osteoporosis has not yet been reported.…”
mentioning
confidence: 99%
“…6,8,31,32 Treatment using teriparatide is associated with a significant increase of bone mass in the lumbar spine. 14,26,28,44 We previously reported that teriparatide administered daily for 2 months before surgery reduced the incidence of pedicle screw loosening after instrumented lumbar fusion in postmenopausal women with osteoporosis, suggesting that teriparatide increased not only bone mass, but also the quality of the pedicle cortex. 34 However, a clinical study of the effect of teriparatide on pedicle screw insertional torque in postmenopausal women with osteoporosis has not yet been reported.…”
mentioning
confidence: 99%
“…While these young, healthy ALN-treated rats did not display any reduction in connectivity deterioration compared to Veh, the addition of ALN to PTH resulted in a significant reduction in connectivity deterioration of both rod and plate trabeculae. The additive effect of combined PTH and anticatabolic therapy is supported by a growing body of existing literature [10,15,16,[45][46][47][48][49]. Our previous work showed that increased trabecular thickening was similar in both PTH and PTHþALN groups, and suggested the additive effect may be related to the higher occurrence of plate-like trabeculae [17].…”
Section: Discussionmentioning
confidence: 93%
“…Combined therapies of antiresorptive treatments and PTH have been proposed and are expected to further increase bone mass. Despite conflicting results in both clinical and preclinical studies [8][9][10][11][12][13][14][15][16], previous work in our lab has shown that combined therapy of PTH and alendronate (ALN), a bisphosphonate, results in an additive effect on bone volume fraction in intact 1 female rats [17]. While combined treatment and PTH monotreatment had a similar effect on stimulating new bone formation and improving trabecular thickness (Tb.Th), the addition of ALN to PTH further improves the relative bone volume and number of plate-versus rod-like structures [17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Muschitz et al [13] investigated women treated with teriparatide for 9 months and then randomized to remain on teriparatide alone or add alendronate or raloxifene plus ongoing teriparatide for an additional 9 months. The BMD gains at the end of the study were significantly greater in both spine and total hip in the teriparatide/alendronate combination group compared to teriparatide alone.…”
mentioning
confidence: 99%